Deconstructing Sharia: A Critical Study of Abdullah Al-Naim's Thought on Naskh - Shofiatul Jannah; Hairus Saleh (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This paper explains how Abdullah al-Naim's sharia formulation serves as a problem-solving solution for numerous issues facing the ummah in recent times. Abdullah al-Naim is a Muslim intellectual who is concerned with reforming Sharia to make it relevant to human rights. This reformation comes from the assumption that the sharia formulation in certain aspects is considered to be irrelevant to modern life. It is even considered to be contrary to universal human rights. So, a demand to build a Sharia model with modern public standards arises, especially in relation to human rights. Using a descriptive-analytic method, this paper concludes that the sharia deconstruction he proposes can be seen as a new approach that is extremely intolerant of the rigidity and uniformity of texts, necessitating the destruction of the text's real meaning. Thus, he introduced a method known as the evolution of Sharia (nasakh), which is seen as a modern ijtihad method. This method for the evolution of Sharia provides a model for creating modern Sharia. The concept of al-Naim’s naskh cannot be taken as it is because rational and scientific validity are used as measures of determining truth, and human values are used as goals by putting aside divine values.